2010
DOI: 10.2752/175303710x12627079939189
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Maltreated Children and Non-Maltreated Children on Their Experiences with Animals—A Japanese Study

Abstract: Recently, studies in the United States, Canada, and Europe have shown that child abuse and animal abuse can coexist in the same household. The implications of these studies are that attention to animal abuse might lead to early detection of, and intervention in, child abuse. Although a promising area of study, in Japan there are no published empirical studies which have examined the relationship between children in abusive families and their companion animals. This study examined the differences between maltre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 7 publications
2
6
0
Order By: Relevance
“…Our results are in general agreement with those reported by Yamazaki (2010) from Japan who found that maltreated children perpetrated more serious acts of abuse than non-maltreated children.…”
Section: Associations With Violence In the Homesupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in general agreement with those reported by Yamazaki (2010) from Japan who found that maltreated children perpetrated more serious acts of abuse than non-maltreated children.…”
Section: Associations With Violence In the Homesupporting
confidence: 93%
“…These figures give us an idea of the number of people who may be at risk of being potential threats to society. The results also indicate that in an AfroCaribbean society, when children harmed animals, males had higher CAI scores, an observation in keeping with other studies in the United States (among others, Flynn, 2001) and in Japan, where male children were more likely than female children to abuse animals (Yamazaki, 2010). However, this link between sex and animal abuse has not been reported by all researchers (Currie, 2006).…”
Section: Gender and Harm Of Animalssupporting
confidence: 87%
See 1 more Smart Citation
“…Boat reported that the instrument was piloted as a structured interview in clinical settings for screening for trauma indicators in hospitalized adolescents. However, the BIARE has been used in only two reported studies, one by Flynn (1999) who modified it for use with a sample of undergraduate students in the United States, and the other by Yamazaki (2010) in a study of maltreated and non-maltreated children in Japan.…”
mentioning
confidence: 99%
“…In a more direct assessment of childhood cruelty to animals, Ascione et al (1997) developed a semi-structured interview for use with children. The Children and Animals Assessment Instrument (CAAI) was field-tested with community and clinical samples of 15 boys and 5 girls (M = 10.4yrs) in day treatment and residential programs for emotionally disturbed youth, incarcerated adolescents, and children accompanying their mothers to shelters for battered women.…”
mentioning
confidence: 99%